A Tale of Two Families: Generational Succession in Filipino and American Family Firms. Issue 2 (July 2015) - McCoy, Alfred W.
Abstract: Through comparison of two families, Filipino and American, this essay finds that the axiomatic three-generational cycle of rise and decline, articulated famously by Andrew Carnegie, proved predictive for an American family firm but not for its Filipino counterpart. Over the span of a century, both families followed a surprisingly similar move from agriculture to food processing and then publishing. Thereafter, however, divergent state policies shaped different destinies for these two families. In the United States, impersonal enforcement of state security and economic regulation allowed the unchecked rise of finance capital that consolidated some 2000 US breweries, most of them family owned, into two transnational corporate conglomerates. In the Philippines, by contrast, persistent rent seeking by elite families, combined with personalised, partisan state economic enforcement, has allowed the continuing dominance of family-controlled corporations. Through comparison of two societies with close relations for over a century, we can see how state economic regulation can encourage the eclipse of major family firms in one society and the perpetuation of a political-economic oligarchy in another.